Curve and instep kick kinematics in elite female footballers - Alcock, A. M.; Gilleard, W.; Hunter, A. B.; Baker, J.; Brown, N. (Journal of Sports Sciences, 2012)
The three-dimensional kinematics of international female footballers performing a simulated direct free kick (curve kick) were compared with those of an instep kick. Reflective markers attached to the participants were tracked by 17 Vicon cameras sampling at 250 Hz. Foot velocity at ball impact did not differ between the two types of kick, but the way in which foot velocity was generated did differ, with instep kicks using a faster approach velocity and greater linear velocities of the hip and knee, and curve kicks using a greater knee angular velocity at impact. In both types of kick, peak knee angular velocity and peak ankle linear velocity occurred at ball impact, providing biomechanical support to the common coaching recommendation of kicking through the ball. To achieve a curved ball trajectory, players should take a wide approach angle, point the support foot to the right of the intended target (for right-footed players), swing the kicking limb across the face of the goal, and impact the ball with the foot moving upwards and in an abducted position. This information will be useful to coaches and players in identifying the fundamental coaching points necessary to achieve a curved trajectory of the ball compared with the more commonly described instep kick kinematics.